'The reports of my death have been greatly exaggerated': China and the developmental state 25 years after Governing the Market. Issue 2 (4th March 2017) - Gabusi, Giuseppe
ABSTRACT: The year 2015 marked the 25th anniversary of the publication of Robert Wade's seminal book Governing the Market (GTM). In his book, Wade elaborates an approach stressing the role of the state in economic development. As the consequences of the Great Recession are forcing many governments and the International Financial Institutions themselves to put into question their ideological stance on unfettered free markets, the anniversary marks the occasion to review the concept of the developmental state (DS) through Wade's GTM approach and re-assess its validity in the twenty-first-century global political economy. Are policy measures historically implemented by the DS still feasible (and desirable) in a globalized era dominated by global value chains? With an eye to the peculiar Chinese experience in the past decades, the paper argues that the key principles in GTM – as properly understood – are still useful as policy prescriptions, as they show how developing countries could successfully start their economic take-off.